The role of packaging and its impact on consumers’ preferences: A case of Azam soft drinks products, Dar es salaam - Mwisho, Mwella, A. (Mzumbe University, 2025)
A dissertation submitted in partial fulfillment of the requirement for the award of the Degree of Master of Business Administration ( MBA-CM) of Mzumbe University